Elaboração de material didático voltado aos alunos de inglês para os negócios com base na linguística de corpus - Rampaso, Marianne (2016)
This study aimed at developing corpus-based teaching materials for Business English students in a private one-to-one class setting. We analyzed the Business English Corpus (Nelson, 2000) in order to find out the most distinctive lexicogramatical and semantic features in Business English area, including both a Sinclairean style analysis of collocations (Sinclair, 1991) and a Biberean style multidimensional analysis of the various registers represented in the corpus (Biber,1988). The theoretical framework for the research was based on Corpus Linguistics, which is an area that is devoted to the study of the language in use through principled collections of spoken and written texts stored on computer (BERBER SARDINHA, 2004; 2009, 2011). In addition,the theoretical framework also included insights on how to use corpora in language teaching from Sinclair (1991; 2004a; 2004b), Johns (1991), Berber Sardinha (2011) and Biber (1988;1999).These insights refer to the exploration of corpora in language teaching through the identification and analysis of lexicogramatical patterns of the language in use and the identification of the lexicogramatical and semantic features in the registers. The results of the corpus analysis showed a great variety of language patterns across the Business English registers. A selection of the patterns found was used in the development of teaching materials, which were then used in class with a particular student. The use of the materials was tracked and documented in a journal, which was later analyzed through a Content Analysis (Bardin, 1977), thereby revealing some of the major ways in which the student and the teacher both interacted with each other and with the materials. The interpretation of this interaction shed new light on how corpora can be used for English language teaching in general and for one-to-one tuition in Business English